SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KARYAWAN TERBAIK MENGGUNAKAN METODE TOPSIS - Hylenarti Hertyana (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2018)
To determine the best employee is not an easy thing for the company because the assessment must be based on the criteria set by the company. Often the determination of the best employees is constrained by the assessment of attendance alone without regard to the ability of the employee's performance whether the employee is able to complete each job well or not. Or assess performance without seeing employee absences and other factors. This SPK uses the Technique for Others Preference method by Similarity to Ideal Solution (TOPSIS). The type of data used in this study is primary data. Primary data is obtained by the author from one property company through direct observation and direct interviews with employees and other relevant parts. This study aims to develop a Decision Support System (SPK) application for determining the best employees in a company. Based on the results of observations and interviews obtained 3 criteria including the Work Period (A1) obtained from the length of time the employee worked, Performance (A2) obtained from employee performance appraisal and Attendance (A3) was obtained from employee attendance conditions. While secondary data is obtained through scientific writing and literature studies. The results of this study produce outputs that meet the objectives and the process of determining the best employees can be more accurate, effective and efficient in producing information that can be used as decision support by the company.